2009
DOI: 10.1210/me.2009-0184
|View full text |Cite
|
Sign up to set email alerts
|

Retinoblastoma Protein Plays Multiple Essential Roles in the Terminal Differentiation of Sertoli Cells

Abstract: Retinoblastoma protein (RB) plays crucial roles in cell cycle control and cellular differentiation. Specifically, RB impairs the G(1) to S phase transition by acting as a repressor of the E2F family of transcriptional activators while also contributing towards terminal differentiation by modulating the activity of tissue-specific transcription factors. To examine the role of RB in Sertoli cells, the androgen-dependent somatic support cell of the testis, we created a Sertoli cell-specific conditional knockout o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(81 citation statements)
references
References 78 publications
5
74
2
Order By: Relevance
“…The mitotic phase of spermatogenesis requires the active E2F-pRb pathway as evidenced by the fact that E2F1 depletion causes highly reduced spermatogonial proliferation and marked testicular atrophy (54). However, upon the initiation of meiosis, activities of the E2F-pRb pathway appear to be down-regulated probably because this suppression allows male germ cells to exit from the mitotic cell cycle and to enter the meiotic program as suggested by several earlier studies (52,(55)(56)(57). In addition, this suppression may enhance the germinal phenotype by inhibiting mitotic proliferating activity and promoting meiotic gene expression (53).…”
Section: Discussionmentioning
confidence: 93%
“…The mitotic phase of spermatogenesis requires the active E2F-pRb pathway as evidenced by the fact that E2F1 depletion causes highly reduced spermatogonial proliferation and marked testicular atrophy (54). However, upon the initiation of meiosis, activities of the E2F-pRb pathway appear to be down-regulated probably because this suppression allows male germ cells to exit from the mitotic cell cycle and to enter the meiotic program as suggested by several earlier studies (52,(55)(56)(57). In addition, this suppression may enhance the germinal phenotype by inhibiting mitotic proliferating activity and promoting meiotic gene expression (53).…”
Section: Discussionmentioning
confidence: 93%
“…The VLDLR gene encodes a canonical receptor of reelin, which is widely involved in neuronal migration in mice and humans (Cheng et al, 2011;Teixeira et al, 2012); therefore, additional studies are needed to determine whether expression of VLDLR is a cause or consequence of aberrant migration. Previous microarray analyses carried out with Rb1-deficient mouse osteoblasts (Sosa-García et al, 2010) and Sertoli cells (Nalam et al, 2009) have also revealed that Vldlr expression is induced upon the loss of Rb1 expression in these cell types. These data suggest the possibility of conserved regulatory mechanisms across different tissues by which RB regulates VLDLR expression to control cell migration or cholesterol homeostasis.…”
Section: Effect Of Rb In Neuronal Migrationmentioning
confidence: 93%
“…Other studies have shown that the RB pathway is crucial in cell cycle control and cell differentiation by serving as a master regulator to coordinate cell cycle exit with differentiation (Lipinski and Jacks, 1999;Nguyen and McCance, 2005;Chinnam and Goodrich, 2011;McDuff and Turner, 2011). It was noted that RB(Ϫ/Ϫ) mice appeared normal by postnatal week 6 (that is, they were fertile with normal testis weights and spermatogenesis indistinguishable from wild-type mice); however, by postnatal weeks 10 to 14, these Rb(Ϫ/Ϫ) mice were infertile with severe Sertoli cell dysfunction, and Sertoli cells displayed defective regulation of multiple androgen-regulated genes and most notably a "leaky" BTB (Nalam et al, 2009). These findings thus illustrate that improper terminal differentiation of Sertoli cells seems not to affect the initial establishment of the BTB to support spermatogenesis in rats, but it fails to "maintain" BTB integrity, which in turn perturbs spermatogenesis.…”
Section: A Sertoli Cell Differentiation Status and Blood-testis Barrmentioning
confidence: 99%